Cofilin reduces the mechanical properties of actin filaments: approach with coarse-grained methods. Issue 12 (28th March 2015) - Kim, Jae In; Kwon, Junpyo; Baek, Inchul; Park, Harold S.; Na, Sungsoo
<x xml:space="preserve">Abstract</x> We applied a coarse-grained molecular dynamics simulation (CGMD) method and constructed elastic network model-based structures, actin and cofilactin filaments. Based on a normal mode analysis, the continuum beam theory was used to calculate the mechanical properties and the results showed good agreement with the established experimental data.